SOCIAL MEDIA, SOCIAL COMPETENCE DAN REMAJA - Khotimatus Sholikhati (Lingkar Studi Komunikasi (LISKI), 2015)
Social media is one of the results of the development new media. It grows with a wide variety of information and technology applications and has a great demand by all levels of society. The use of social media can provide a dual effect on the social fabric of society, especially the youth, because youth are the active users of social media. Students as a young generation need to be prepared with digital media literacy skills to be able to use digital media intelligently and effectively. This study aims to determine the ability of the digital media literacy of students STIKOM LSPR Jakarta, in particularly of the usegae of social media. The research used the instrument of Social Competence Framework based on European Commission (2009) to determine the level of digital media literacy of students. The results showed that the media literacy of students STIKOM LSPR including medium level based on their social competence. Moreover, the result can be used as a foundation in creating digital media literacy education programs.